Bioclimatic design strategies simulated in a housing module in Arequipa - Perú for thermal comfort and energy saving - Zúñiga Hernández, José Andrew (2018)
The objective of this research is to identify the most suitable bioclimatic design strategies to achieve thermal comfort and energy savings in building in the city of Arequipa-Peru. The proposed housing module is the first simulated housing module in the city of Arequipa-Peru, a city with a housing deficit of 86,817 homes (INEI, 2007), with a particular population and a material of the place called “sillar” or volcanic tuff. The type of research is quantitative, deductive and analytical. The mothod used is as follows, first a basic module has been created, which has been simulated with the “Design Builder” program with the characteristics of a 77 m2 house of a family of low socioeconomic status, with exposed brick walls and simple glass windows. Bioclimatic strategies are applied to this basic module, such as the use of local material (sillar), the addition of a small greenhouse and solarium (lamppost), which were compared with the basic module, leading to the creation of a module housing for the city which has a global improvement of 14% in its consumption and 74% in the global of demands with respect to the basic module.